2000
DOI: 10.1093/ajcn/71.5.1270s
|View full text |Cite
|
Sign up to set email alerts
|

Role of cholesterol in embryonic development

Abstract: We showed previously that 3 distal inhibitors of cholesterol synthesis are highly teratogenic in rats. AY 9944 and BM 15766 inhibit 7-dehydrocholesterol reductase, which catalyzes the last step of cholesterol synthesis, and triparanol inhibits Delta(24)-dehydrocholesterol reductase, which catalyzes the last step in another pathway. These molecules cause holoprosencephalic brain anomalies. Under certain experimental conditions, other anomalies (of the limbs and male genitalia) are also observed. Assays performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
1
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(79 citation statements)
references
References 32 publications
1
76
1
1
Order By: Relevance
“…This gene is responsible for the proper development of tissues and for the organization of embryonic tissue. SHH regulating protein must bind to cholesterol to be active 93 . Hypocholesterolemia is also related to decreases in some plasma proteins.…”
Section: Clinical Consequences Of Hypocholesterolemiamentioning
confidence: 99%
“…This gene is responsible for the proper development of tissues and for the organization of embryonic tissue. SHH regulating protein must bind to cholesterol to be active 93 . Hypocholesterolemia is also related to decreases in some plasma proteins.…”
Section: Clinical Consequences Of Hypocholesterolemiamentioning
confidence: 99%
“…Cholesterol also provides the structural scaffolding for the synthesis of steroids a n d s t e r o i d h o r m o n e s , a n d f o r t h e biosynthesis of bile and bile acid salts. Sterol plays also an important role in embryonic development (Roux et al, 2000). …”
mentioning
confidence: 99%
“…Furthermore, the highest expression of Xdhcr7 was detected by RT-PCR analysis from early gastrulation to early organogenesis stages, a time-window during which different tissue and organ identities are established. The general role of cholesterol in embryonic development is well described (Wolf, 1999;Moebius et al, 2000;Roux et al, 2000;Kelley and Herman, 2001). The early expression of Xdhcr7 is in accordance with the multiple developmental defects reported in DHCR7 mutations (Porter, 2000;Waterham and Wanders, 2000;Nowaczyk and Waye, 2001;WitschBaumgartner et al, 2001;Ciara et al, 2004), since the reported phenotypes may result from a failure of early patterning events.…”
Section: The Expression Of Xdhcr7 Is Spatially Restricted and Overlamentioning
confidence: 99%
“…It is interesting to note that recently a connection between Hedgehog signaling and the PCP pathway has been elucidated in Xenopus (Park et al, 2006). In fact, with regard to the wide spectrum of functions fulfilled by cholesterol in vertebrates (Wolf, 1999;Incardona and Eaton, 2000;Roux et al, 2000;Herz and Bock, 2002;Pfrieger, 2003a,c), a perturbation of cholesterol biosynthesis is likely to affect multiple cellular processes, among which Hh signalling may be one of the most sensitive.…”
Section: Loss Of Xdhcr7 Function Impairs the Early Establishment Of Nmentioning
confidence: 99%